2016
DOI: 10.1007/s11920-016-0689-y
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Drug Use and the Developing Brain

Abstract: Adolescence is an important neurodevelopmental period marked by rapidly escalating rates of alcohol and drug use. Over the past decade, research has attempted to disentangle pre- and post-substance use effects on brain development by using sophisticated longitudinal designs. This review focuses on recent, prospective studies and addresses the following important questions: (1) what neuropsychological and neural features predate adolescent substance use, making youth more vulnerable to engage in heavy alcohol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(122 citation statements)
references
References 97 publications
(117 reference statements)
4
118
0
Order By: Relevance
“…Previously reported NAC-related reductions in marijuana use could generalize to other substances including alcohol. Effective interventions during adolescence could have substantial long-term implications by reducing acute and enduring negative social, academic, and cognitive consequences related to binge adolescent drinking (Squeglia & Gray, 2016). Evaluation of novel candidate treatments, including NAC, is warranted in adolescents, particularly in regards to interventions that effectively reduce alcohol given its high use rates during adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported NAC-related reductions in marijuana use could generalize to other substances including alcohol. Effective interventions during adolescence could have substantial long-term implications by reducing acute and enduring negative social, academic, and cognitive consequences related to binge adolescent drinking (Squeglia & Gray, 2016). Evaluation of novel candidate treatments, including NAC, is warranted in adolescents, particularly in regards to interventions that effectively reduce alcohol given its high use rates during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Several adverse outcomes are associated with adolescent alcohol and marijuana use, including poorer psychosocial (Miller, Naimi, Brewer, & Jones, 2007), cognitive (Jacobus et al, 2015; Meier et al, 2012; Nguyen-Louie et al, 2015; Squeglia & Gray, 2016; Squeglia, Spadoni, Infante, Myers, & Tapert, 2009), and educational outcomes (Latvala et al, 2014). Unfortunately, few adolescent substance use treatment options exist and current efforts have only been modestly effective (Jensen et al, 2011; Tripodi, Bender, Litschge, & Vaughn, 2010; Vandrey & Haney, 2009), with some studies suggesting up to 86% of youth return to alcohol or drug use within 12 months following treatment (Brown, Gleghorn, Schuckit, Myers, & Mott, 1996; Winters, Stinchfield, Opland, Weller, & Latimer, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Imaging studies using different modalities have consistently reported that alcohol use during adolescence is associated with abnormalities in brain structure, function and connectivity [72]. However, the critical question of whether these anomalies are consequences of alcohol abuse or preexisting vulnerability factors for early use and misuse remains unanswered in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Control participants with a history of heavy alcohol or drug use were also excluded due to known associated functional and structural abnormalities. 46 Heavy alcohol use was defined as a score higher than eight on the Alcohol Use Disorders Identification Test (AUDIT). 47 Heavy drug use was defined by clinicians of the ICCAM team using the following criteria: more than 300 pills (lifetime) for MDMA; daily/almost daily THC use for more than one year and more than 2 spliffs; and more than once a week for more than six months and more than 1 g for amphetamines.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%